Urban gun violence: self-help organizations as healing sites, catalysts for change, and collaborative partners - Delgado, Melvin (Interpersonal violence series, 2021)
"Gun violence is a national threat and no more so than in the nation's urban communities, particularly taking its toll on people of color. Urban violence focused self-help organizations are vehicles for the dead to speak to us, and let us not forget that they once lived among us. These voices get captured and amplified through these organizations - their family become our family. The headlines their deaths created are not allowed to get relegated to history and continue to live giving meaning to a profound social justice cause. This book honors those who have died and continuing to give voice to their lives and preventing others from joining this chorus. The theme that we must forgive ourselves before we can forgive the offender is strong and pervasive among those who are survivors and engaged in self-help initiatives"--